New method of hand anastomosis to complete the Duhamel operation for Hirschsprung′s disease - Adeniran J; Abdur-Rahman L; Odi T (Wolters Kluwer Medknow Publications, 2008)
Objective/Purpose: This paper describes a new method of hand anastomosis to complete the Duhamel operation for Hirschsprung′s disease (HD). Methodology: All patients had diagnosis of Hirschsrung′s disease confirmed by rectal biopsy and had defunctioning colostomy. At the definitive operation, the ganglionic bowel was brought down in a retro-rectal position and anastomosed at the anal canal just above the dentate line. At this anastomosis, the sutures at 11 and 1 o′clock were left long as stay sutures. An incision was then made down the new bowel at the antimesenteric border from the pelvic brim. Another incision was made down the back of the native rectum. A long-curved artery forceps was then passed into the incision in the native rectum out of the anal canal. This forceps was now hooked round the anastomosis at 12 o′clock and further pushed in until the point appears through the colotomy in the ganglionic bowel. The two layers of bowel between the forceps were incised. The forceps was now inserted to grab the long sutures at 11 o′clock and 1 o′clock in turn, and delivered through the pelvis. Anastomosis between the edges of the native rectum and the neorectum was then done with interrupted PDS inside and silk outside. Results: Seven patients had the procedure done. Age ranged between 4 months and 4 years (mean 3.4 years). They were all males. One patient died early in the series from reaction to postoperative analgesia. Four older patients have bowel motions 2-3 times per day, do not soil at night, and are fully continent. Conclusion: This preliminary study shows that hand anastomosis could be used to complete Duhamel operation for patients with HD with satisfactory early results.